Low doses of glyphosate enhance growth, CO2 assimilation, stomatal conductance and transpiration in sugarcane and eucalyptus - Nascentes, Renan F [UNESP]; Carbonari, Caio A [UNESP]; Simões, Plinio S [UNESP]; Brunelli, Marcela C [UNESP]; Velini, Edivaldo D [UNESP]; Duke, Stephen O (Wiley, 2018)
INTRODUCTION: Sublethal doses of herbicides can enhance plant growth and stimulate other process, an effect known as hormesis. The magnitude of hormesis is dependent on the plant species, the herbicide and its dose, plant development stage and environmental parameters. Glyphosate hormesis is well established, but relatively little is known of the mechanism of this phenomenon. The objective of this study was to determine if low doses of glyphosate that cause growth stimulation in sugarcane and eucalyptus concomitantly stimulate CO2 assimilation. RESULTS: Shoot dry weight in both species increased at both 40 and 60 days after application of 6.2 to 20.2 g a.e. ha−1 glyphosate. The level of enhanced shoot dry weight was 11 to 37%, depending on the time after treatment and the species. Concomitantly, CO2 assimilation, stomatal conductance and transpiration were increased by glyphosate doses similar to those that caused growth increases. CONCLUSION: Glyphosate applied at low doses increased the dry weight of sugarcane and eucalyptus plants in all experiments. This hormetic effect was related to low dose effects on CO2 assimilation rate, stomatal conductance and transpiration rate, indicating that low glyphosate doses enhance photosynthesis of plants. © 2017 Society of Chemical Industry.
Keywords: Eucalyptus sp.; hormesis; low doses; Saccharum spp.